SISTEM PENGOLAHAN DATA PENERIMAAN SISWA BARU DAN PEMBAYARAN SPP PADA SMK KARYA GUNA 1 BEKAS - Indra Sadikin; Uus Rusmawan (Universitas Methodist Indonesia, 2017)
Data processing system of admission on the acceptance of new learners (PPDB) that still use the manual way i.e. by processing the data in a Microsoft Excel application so that new students admissions section should check the files of prospective applicants to be processed as data prospective students who will follow some test selection organized schools, new students admissions section of the process data of the number of students enrolling , prospective students are accepted or failed, theorigin of the school's Registrar by using Microsoft Excel so the data accuracy error is still happening, for the payment of the contributions of coaching education (SPP) which is still manual which required administrative staff looking for the names of students who make payment so it takes time and need to be left Coaching Education Donation payment cards because the payment transaction process Coaching Education Donation in a day can be more than 3 transactions. Computerized data processing system of admission and payment of TUITION FEE-based desktop allows acceptance section allows new learners can create your prospective students with accurate, administrative part allows can make the transaction process rapidly so there is no need to leave the coaching Education Donation payment card in place so that new students admissions section and make the proper reports and quick.